APLIKASI MODEL ARTIFICIAL NEURAL NETWORKS UNTUK STOCK FORECASTING DI PASAR MODAL INDONESIA - Christian Herdinata (Jurnal Keuangan dan Perbankan, 2010)
This research showed the applicat ion of model Art if icial Neural Networks (ANN) orJaringan Syaraf Tiruan (JST) at the f ield of monetary science, especially for the applicat ion off inancial forecast ing. ANN or JST was a new alternat ive for the applicat ion of f inancialforecast ing.The purpose of this research was to know whether the stock index instantaneouslyand fully ref lect historical informat ion, in Indonesia Stock Exchange (IDX). The research usedcomparison between return of technical t rading rule based Art if icial Neural Networks (ANN)model and return of buy hold st rategy. The result showed that the weakness form ofef f icient market hypothesis was rejected in the Indonesian capital market . Expectat ion ofthis research was giving informat ion and securing the market perpet rators that st ill enabledto get abnormal of return by doing commerce in chnical through forecast ing of model Art ificial Neural Networks (ANN) or Jaringan Syaraf Tiruan ( JST).